Riwayat Penyakit Malaria bagi Pertumbuhan dan Perkembangan Balita - Tiyan Febriyani Lestari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine whether there is a relationship between a malaria history and toddlers' growth and development at the Sentani Health Center, Jayapura Regency. The method used is descriptive, using a cross-sectional approach. The results showed that of the 96 children examined, most had a history of malaria in the last year, namely 73 people (76.04%). The results of the bivariate analysis found a p-value > 0.05. In conclusion, there is no relationship between a history of malaria and the growth of children under five, and there is no relationship between a history of malaria and the development of children under five. Keywords: Toddlers, Development, Growth, History of Malaria